Hyperthermia effects on Hsp27 and Hsp72 associations with mismatch repair (MMR) proteins and cisplatin toxicity in MMR-deficient/proficient colon cancer cell lines - Sottile Fleury, Mayra Lis (2015)
Purpose: Hyperthermia is used in combination with conventional anticancer agents to potentiate their cytotoxicity. One of its key events is the synthesis of heat shock proteins (HSPs), which are able to associate with components from DNA repair mechanisms. However, little is known about their relationship with the mismatch repair system (MMR). Our aim was to study the effects of hyperthermia on cisplatin (cPt) sensitivity and to determine whether MLH1 and MSH2 associate with Hsp27 and Hsp72 in MMR-deficient(-)/-proficient(+) cells.Materials and methods: HCT116+ch2 (MMR-) and HCT116+ch3 (MMR+) cell lines were exposed to cPt with or without previous hyperthermia (42 °C, 1 h). Clonogenic survival assays, MTT, confocal immunofluorescence, immunoprecipitation, immunoblotting and flow cytometry were performed.Results: Hyperthermia increased the cPt resistance in MMR- cells 1.42-fold. Immunofluorescence revealed that after cPt, Hsp27 and Hsp72 translocated to the nucleus and colocalisation coefficients between these proteins with MLH1 and MSH2 increased in MMR+ cells. Immunoprecipitation confirmed the interactions between HSPs and MMR proteins in control and treated cells. Hyperthermia pretreatment induced cell cycle arrest, increased p73 expression and potentiated cPt sensitivity in MMR+ cells.Conclusions: This is the first report showing in a MMR-/+ cellular model that MLH1 and MSH2 are client proteins of Hsp27 and Hsp72. Our study suggests that p73 might participate in the cellular response to hyperthermia and cPt in a MMR-dependent manner. Further functional studies will confirm whether HSPs cooperate with the MMR system in cPt-induced DNA damage response or whether these protein interactions are only the result of their chaperone functions.